Herbert Marcuse Tentang Masyarakat Satu Dimensi - Agus Darmaji (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
As an inspirator of the new left movement, Marcuse’s doctrine on socio-political system is considered more radical than orthodox communist. His admirers even give to him a nickname ‘a prophet’: prophet who became inspirator for student revolution in 1968; prophet for hippy and flower generation; prophet who voiced their opinion; prophet who advanced phenomenon which emerged and threatened the world and human race. History has noted that man in the modern industrial community has opportunity to fulfill his needs. In fact, he is really hampered by repressive condition. The measure of rationality in the society is technological rationality. Man and society are within technological trap, domination and manipulation. Technology can replace man’s power not just in industrial field, but in whole life chain. Technology which was previously made to be emancipatorical tool from the natural wildness, now is used to coerce and repress human being. As such, the most dominant view in the modern industrial society is ‘repressive toleration,’ i.e. toleration that is impressed as giving great freedom, in fact it is coercive.